Peran Orientasi Inovasi terhadap Kinerja UMKM yang Dimoderasi oleh Intensitas Persaingan - Naim, Abu; Ambarwati, Rina; Permananingrum, Ervina Yennie; Hadi, Ilwin; Pauji, Ahmad (Jurnal Bisnis dan Kewirausahaan, 2025)
The purpose of this study is to determine whether Innovation Orientation (IO) has an impact on the performance of micro, small, and medium enterprises (MSMEs) moderated by Competition Intensity (CI) in the food and beverage sector in Indonesia. The research sample consisted of 100 MSME actors. Sample collection was conducted through an online questionnaire. The analysis used in this study employed Smart PLS 3.0. The results showed that IO had a direct positive impact on MSME performance, but CI did not have a direct positive impact and did not moderate MSME performance. These findings provide applicable guidance for MSME owners and policymakers that encouraging innovation through internal support systems and market responsiveness can yield tangible performance benefits, even in highly competitive environments.